The Demise of Works Councils in Germany - Susanne Kohaut; Claus Schnabel (Institute of Labor Economics (IZA), 2024)
This paper documents and analyses the demise of works councils in Germany in the period 2007-2022. Using representative panel data, we show that the share of plants with a works council has fallen substantially in the private sector but not in the public sector. Almost two-thirds of workers in the private sector in Germany are not covered by worker co-determination anymore. We present first evidence that firm dynamics (i.e. entries and exits of firms) seem to be one contributory factor to the reduction in works council coverage over time. Multivariate analyses indicate that three variables play an important role in explaining the (non-)existence and the dissolution of works councils. These are plants' decreasing coverage by collective bargaining agreements, the growing relevance of alternative, non-statutory forms of worker representation, and the owner-management of a plant. As our results paint a bleak picture for the future of plant-level co-determination in Germany, we critically discuss a number of policy measures to stabilize works council prevalence.
Keywords: J53; M50; 330; works council; co-determination; worker participation; Germany